Effects of Shilajit Nanoparticles on Semen Quality in Rats Exposed to Cadmium Chloride - Jalil, Noor Saad; Al-Zamely, Hayder A. N. (American Journal of Biomedicine and Pharmacy, 2025)
This study investigated the protective and enhancing effects of green-synthesized zinc oxide nanoparticles from shilajit extract on sperm quality in rats subjected to cadmium-induced oxidative stress. Shilajit extract was used to synthesize ZnO nanoparticles. Sixty male rats were divided into four groups (n=15): a negative control (T1), a positive control exposed to cadmium chloride (2 mg/kg BW) (T2), a group receiving only shilajit nanoparticles (200 mg/kg BW) (T3), and a group receiving both cadmium and shilajit nanoparticles (T4). After 30 days, semen analysis was performed to assess sperm concentration, motility, viability, and abnormality. Cadmium exposure (T2) caused a severe decline in all sperm quality parameters compared to the control (p < 0.05). Co-administration of shilajit nanoparticles (T4) significantly ameliorated these negative effects, restoring values closer to the control group. Remarkably, the group treated with shilajit nanoparticles alone (T3) exhibited sperm parameters (concentration: 97.46 ± 0.45 million/mL, motility: 95.46%, viability: 95.23%, abnormality: 1.37%) that were significantly superior to those of the healthy control group. The findings demonstrate that shilajit-synthesized ZnO nanoparticles not only confer significant protection against cadmium-induced reproductive toxicity but also possess intrinsic spermatogenic-enhancing properties, highlighting their potential as a therapeutic agent for improving male fertility.